Policing a riot-torn city: Kolkata, 16–18 August 1946. Issue 1 (2nd January 2017) - Samaddar, Ranabir
ABSTRACT: Calcutta is now known as Kolkata, but for the purposes of this article, Calcutta is retained throughout. Historical accounts of the Great Calcutta Riots (1946) emphasize their role in making Indian Partition an inevitable outcome of nationalist-religious politics in colonial India. It is seen as a critical event in the religious wars, conventionally known as the Partition riots or communal riots, in the Indian sub-continent in 1945–47. This article, while basing itself on previous historical understanding, views the Great Calcutta Killings as a remarkable event in the mutually constitutive relations between the police and the crowd. The police apparatus built by the colonial state was based fundamentally on the obedience of individuals and individual subjection to the institution of law and order when the feudal form of allegiance was no longer required. Their conduct was now required to demonstrate total and exhaustive obedience to whatever the imperatives of the colonial state were in relation to protection of the economy, commerce, trade, education, health, territory and security of life. The success of the apparatus depended on a smooth interrelation of these imperatives and thus between different functions of the police. The Calcutta Riots showed that there may be moments when the smooth relations break down, when all bounds of obedience are broken, and populations imagine their conduct not in juridical terms, but in other possible frames. In other words, politics will no longer be conducted in a civilian frame, but in the frame of war—one more reason to think of the riots as a moment in a war. In those moments, the link between the reason of state and that of the government may collapse. In this context, the Calcutta Riots further tell us (a) how borders within a city emerge in situations of violence and how an event like the Calcutta Riots dispels the myth that the city is an organic unity unaffected by borders and boundary-making exercises; and (b) how the failure of the Calcutta Riot Enquiry Commission to conclude its findings demonstrated the closure of legal logic.